Look who's talking too [videorecording (DVD)] - Travolta, John, 1954-; Alley, Kirstie; Dukakis, Olympia; Brooks, Mel, 1926-; Gottfried, Gilbert, 1955-2022; Heckerling, Amy (Columbia/TriStar, 2000)
Little Mikey figures he's got it made after uniting his mother with the dad of his dreams. But instead of family bliss, Mikey gets the biggest surprise of his life- a baby sister.